Old age and underlying interstitial abnormalities are risk factors for development of ARDS after pleurodesis using limited amount of large particle size talc. Issue 1 (4th October 2017) - Shinno, Yuki; Kage, Hidenori; Chino, Haruka; Inaba, Atsushi; Arakawa, Sayaka; Noguchi, Satoshi; Amano, Yosuke; Yamauchi, Yasuhiro; Tanaka, Goh; Nagase, Takahide
ABSTRACT: Background and objective: Talc pleurodesis is commonly performed to manage refractory pleural effusion or pneumothorax. It is considered as a safe procedure as long as a limited amount of large particle size talc is used. However, acute respiratory distress syndrome (ARDS) is a rare but serious complication after talc pleurodesis. We sought to determine the risk factors for the development of ARDS after pleurodesis using a limited amount of large particle size talc. Methods: We retrospectively reviewed patients who underwent pleurodesis with talc or OK‐432 at the University of Tokyo Hospital. Results: Twenty‐seven and 35 patients underwent chemical pleurodesis using large particle size talc (4 g or less) or OK‐432, respectively. Four of 27 (15%) patients developed ARDS after talc pleurodesis. Patients who developed ARDS were significantly older than those who did not (median 80 vs 66 years, P  = 0.02) and had a higher prevalence of underlying interstitial abnormalities on chest computed tomography (CT; 2/4 vs 1/23, P  < 0.05). No patient developed ARDS after pleurodesis with OK‐432. This is the first case series of ARDS after pleurodesis using a limited amount of large particle size talc. Conclusion: Older age and underlying interstitial abnormalities on chest CT seem to be risk factors for developing ARDS after talc pleurodesis. Abstract : Talc pleurodesis can cause acute respiratory distress syndrome (ARDS), but this rarely occurs with a limited amount of large particle size talc. We present four patients who developed ARDS after talc pleurodesis. Age and presence of interstitial abnormalities on chest computed tomography (CT) may be risk factors for ARDS after talc pleurodesis.